68th Annual Meeting of the German Society of Neuropathology and Neuroanatomy (DGNN) - Meeting Abstracts, September 12–14, 2024 - German Society of Neuropathology; Neuroanatomy (DGNN) (Free Neuropathology, 2024)
Dear colleagues, It is my pleasure and honor to host the 68th Annual Meeting of the German Society of Neuropathology and Neuroanatomy (DGNN) in Regensburg. Since the Magdeburg meeting in 2019 this is the first pure national meeting of our society that will be held in presence after five long years. While the meeting in 2020 was cancelled due to the Corona pandemic, the 2021 meeting (organized by the colleagues in Gießen) took place as a mere online meeting. In 2022 and 2023 our national society meetings were embedded in the “Neurowoche” and the International Congress of Neuropathology in Berlin. We are enthusiastic about this years’ reunion of our society in Regensburg. In our Regensburg meeting, we aim to provide a comprehensive update on the major and hot topics in neuropathology. Neuropathologists address some of the currently most relevant and discussed health care issues, such as for example cancer, neuroimmunological diseases like Multiple Sclerosis, neurodegenerative diseases including Alzheimer’s and Parkinson’s, and muscle/nerve diseases. As tissue specialists, neuropathologists directly study diseases in human materials. Neuropathologists use state of-the-art methods to uncover disease processes on the molecular level. During our congress, we will hear a lot on the methodical progress made in this regard. Neuropathology is also becoming increasingly clinical as many of our scientific and diagnostic findings influence and directly guide treatment decisions. We were able to attract renowned national and international speakers and our meeting will allow for an intensive interchange both within our society and with our neighboring disciplines. Program highlights include a Pre-Congress hands-on Workshop on Next Generation Sequencing, a session on Molecular Tumorboards and a Mini-Symposium on Quality Assurance in Neuropathology. We are delighted about the submission of 31 abstracts covering the research fields Neurooncology, Neuroimmunology, Muscle/Nerve, Neurodegeneration, and Methods/Free Topics. The abstracts are published below in this edition of Free Neuropathology. I want to thank the scientific committee of our congress for helping in evaluating the submissions and selecting the poster talks and poster spotlight presentations. Many of the abstracts were submitted by our young researchers. They deserve our special attention! Posters will be exhibited throughout the entire congress and we will have plenty of time for poster viewing and discussions on Thursday evening at the Welcome Reception and at the main poster session on Friday at noon. So let me again welcome you all to our beautiful city of Regensburg. I am looking forward to inspiring talks, vivid discussions and enriching encounters with like-minded people. Yours, Prof. Dr. Markus J. Riemenschneider Regensburg University Hospital, Department of Neuropathology Congress President DGNN Annual Meeting 2024